CytroCell: Valued Cellulose from Citrus Processing Waste - Antonino Scurria; Lorenzo Albanese; Mario Pagliaro; Federica Zabini; Francesco Giordano; Francesco Meneguzzo; Rosaria Ciriminna (Molecules, 2021)
Isolating cellulose from citrus processing waste without employing chemicals has so far been an unfulfilled goal of chemical research applied to the valorization of a widely available biowaste, annually totaling >100 million tonnes. We have applied hydrodynamic cavitation using a Venturi-type reactor for the extraction of all valued bioproducts of industrial citrus processing waste in water only, directly on a semi-industrial scale. After reporting the discovery of IntegroPectin in the soluble fraction of the aqueous extract, we now report the isolation of a cellulosic material in the water-insoluble fraction of cavitated lemon and grapefruit processing waste. Named “CytroCell”, the material is cellulose of low crystallinity, high porosity, good water holding capacity and good dispersibility in water. These properties open the route to mass-scale production of a useful functional material from a cheap and abundant biowaste.